Capturing the life cycle of false hair products to identify opportunities for remanufacture - Nicky Wilson; Avril Thomson; Karena Moore-Millar; Winifred Ijomah (Journal of Remanufacturing, 2019)
The false hair industry represents a case of growing demand and depleting natural resources, in addition to a significant environmental impact of synthetic alternatives. Despite the growth of the false hair industry, there is a lack of research to date regarding the complete life cycle of false hair products. False hair products currently follow a linear life cycle with a cradle-to-grave flow of materials, making it essential that consideration is given to how such products are produced, used and disposed of. To reduce the strain on the supply of raw materials, limit the environmental impact of synthetic materials and ensure end users receive quality products at a reasonable price, there is a need to transform the current cradle-to-grave life cycle of false hair products. This research aims to capture the life cycle of false hair products and identify opportunities to sustainably capture waste within that life cycle. The study involved desktop research, an extensive user survey, manufacturer survey, an overview of the medical demand for false hair products and interviews with wig banks to capture for the first time the life cycle of false hair products. Recycling, reconditioning and remanufacture of waste materials are identified as mechanisms to reduce waste of false hair products within the UK industry, with potential for this research to impact on an international scale by reducing the global demand for natural raw materials and limiting the environmental impact of synthetic fibres.
Keywords: 650; Remanufacture; Circulareconomy; False hair products; Lifecycleanalysis; Human hair